Integrating anthropogenic material stocks and flows into a modern resource classification framework: Challenges and potentials. (1st October 2016) - Winterstetter, A.; Laner, D.; Rechberger, H.; Fellner, J.
Abstract: In light of various policy initiatives promoting the efficient use of resources, this study investigates how anthropogenic resources could be classified under the United Nations Framework Classification for Fossil Energy and Mineral Reserves and Resources 2009 (UNFC-2009). Compared to geogenic resources, anthropogenic deposits are more heterogeneous and subject to various dynamics, due to the human impact on their genesis. Often they must be assessed not only under aspects of resource recovery, but with respect to alternative waste treatment and disposal options. Factors, which are influencing the classification of anthropogenic resources, vary during the individual phases of resource classification, namely prospection, exploration and evaluation. During the (pre)prospection phase, the preconditions defining the setting for the following resource classification are checked, i.e. the deposit's status of availability for mining ("in-use stocks", "obsolete stocks" or "waste flows") as well as the specific handling and mining condition. System variables, which determine the potentially extractable amount of materials, play a major role during the exploration phase, e.g. technological choices for recovery. In the evaluation phase, modifying factors with direct impact on the project's economics are investigated, such as prices for secondary products, (avoided) costs and possibly monetized externalities. Challenges and potentials of classifying different types of anthropogenic resources under UNFC-2009 are illustrated for two different cases: Mining an old landfill (obsolete stock) is contrasted in a qualitative discussion to mining E-waste (waste flow). Finally, an operative evaluation procedure is outlined, which is still to be refined and illustrated via case studies. Highlights: The resource classification system UNFC-2009 is applied to anthropogenic resources. Differences between anthropogenic and geogenic resources are analyzed. A general operative procedure for the classification of anthropogenic resources is outlined. Mining an old landfill (obsolete stock) is contrasted to mining E-waste (waste flow). Potentials and challenges of applying UNFC-2009 to anthropogenic resources are discussed.